Low‐frequency ventilation during cardiopulmonary bypass for lung protection: A randomized controlled trial. Issue 6 (2nd May 2019) - Fiorentino, Francesca; Jaaly, Emad Al; Durham, Andrew L.; Adcock, Ian M.; Lockwood, Geoffrey; Rogers, Chris; Ascione, Raimondo; Reeves, Barney C.; Angelini, Gianni D.
Abstract: Objective: Pulmonary dysfunction is a common complication in patients undergoing heart surgery. Current clinical practice does not include any specific strategy for lung protection. To compare the anti‐inflammatory effects of low‐frequency ventilation (LFV), as measured by nuclear factor κ‐light‐chain‐enhancer of activated B cells (NF‐κB) p65 pathway activation, for the entire cardiopulmonary bypass (CPB) vs both lungs left collapsed in patients undergoing coronary artery bypass grafting (CABG). Methods: Two groups parallel randomized controlled trial. The primary outcome was inflammation measured by NF‐κB p65 activation in pre‐ and post‐CPB lung biopsies. Secondary outcomes were additional inflammatory markers in both biopsy tissue and blood. Results: Thirty‐seven patients were randomly allocated to LFV (18) and to both lungs left collapsed (19). The mean concentration of NF‐κB p65 in the biopsies before chest closure (adjusted for pre‐CPB concentration) was higher in the LFV group compared to both lungs left collapsed group but this was not significant (0.102, 95% confidence interval, −0.022 to 0.226, P  = 0.104). There were no significant differences between groups in the other inflammatory markers measured in tissue and blood. Conclusions: In patients undergoing elective CABG, the use of LFV during CPB when compared to both lungs left collapsed does not seem to reduce inflammation in lung biopsies and blood.